Variant Design of Girder-Slab Structure with Different Geometric Cells Under Flexural Vibrations - Andrey A. Chernyaev; Kirill V. Marfin (Structural Mechanics of Engineering Constructions and Buildings)
Girder-slab structures are widely used in industrial buildings, bridge decks, complex combined engineering structures and other objects of construction and mechanical engineering. An important task in their design is to find the most economical structural solution with the least amount of material while ensuring the necessary strength and rigidity. Therefore, the development of methods and algorithms for searching of the most rational and optimal design solutions is of great significance. The authors offer a technique of variant design of girder-slab structures with various cell shapes: rectangular, triangular, rhombic, trapezoidal and other, when analyzing vibrations. The technique is based on the principles of physicomechanical analogies and geometrical methods of structural mechanics. For a numerical example, a cantilever girder-slab structure on trapezoidal base is studied. The bars are of typical sections, the flooring is smooth steel. It is shown that cell geometry affects flexural vibrations of the girder-slab structure and material consumption.